Multiple part umbilical cord entanglement and neonatal outcomes - Tasuku Mariya; Yuya Fujibe; Shota Shinkai; Naoko Sugita; Masahiro Suzuki; Toshiaki Endo; Tsuyoshi Saito (Elsevier, 2018)
Objective: Umbilical cord entanglement is known to be a major cause of fetal hypoxia and to be correlated with several neonatal complications, but almost all of the previous reports were restricted to nuchal cord. In this study, we retrospectively examined the correlation between multiple part cord entanglement and pregnancy outcomes. Materials and methods: A total of 2156 cases were recruited from term deliveries in our hospital from 2008 to 2012. We counted umbilical cord loop numbers not only for nuchal cord but also for trunk and limb cord entanglement. We classified the cases into three groups: no loop, single loop and multiple loops group. We statistically analyzed pregnancy outcomes statistically in the three groups. Results: One thousand, four hundred and fifty-eight cases had no cord entanglement, 594 cases had single loop entanglement and 104 cases had multiple loops entanglement. Values of umbilical artery blood, pH (p = 0.002) and base excess (p < 0.001) showed significantly unfavorable status in entanglement cases, especially in the multiple loops group. A significantly larger percentage of neonates in the multiple loops group needed for oxygen (p < 0.001). Conclusion: Multiple umbilical cord entanglement is highly correlated with early neonatal unfavorable status and need for resuscitation. Keywords: Umbilical cord entanglement, Nuchal cord, Trunk and limb cord, Multiple entanglement, Neonatal resuscitation